2019
DOI: 10.1007/s40203-019-0052-1
|View full text |Cite
|
Sign up to set email alerts
|

Computational insight to putative anti-acetylcholinesterase activity of Commiphora myrrha (Nees), Engler, Burseraceae: a lessen of archaeopharmacology from Mesopotamian Medicine I

Abstract: Commiphora spp., Burseraceae family and their resinous matter, myrrh, are used in Mesopotamian medicine as fragrance or antiinsectant. Based on in vitro, leaves, bark, and resin methyl alcohol extract of C. myrrha showed similar inhibitory effects of 17.00, 26.00, and 29.33% for acetylcholinesterase (AChE) as compared to eserine, respectively. The ADMET properties and putative anticholinesterase activity of phytochemicals of myrrh were computationally predicted using in silico tools. Phytochemicals of C. myrrh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…In a molecular simulation study performed by Hussein et al (2019), it was found that the bicyclic sesquiterpene δ-cadinene, present in the total extract of the Commiphora myrrha (Nees) plant, bound to the human AChE with a very high affinity of -9.2 kcal/mol, and formed hydrophobic contacts with Trp83, Phe330 and His439 residues localized in the catalytic triad of the enzyme (Hussein et al, 2019). In another in silico study, δ-cadinene exhibited a binding affinity of -6.77 kcal/mol to AChE, the target protein of Alzheimer's disease, and formed pi-alkyl bonds with polar aliphatic residues Trp286 and His447, and hydrophobic contacts with hydrophobic residues Tyr124 and Phe295 (da Silva Barbosa et al, 2020).…”
Section: Molecular Docking Results Of Essential Oil Major Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a molecular simulation study performed by Hussein et al (2019), it was found that the bicyclic sesquiterpene δ-cadinene, present in the total extract of the Commiphora myrrha (Nees) plant, bound to the human AChE with a very high affinity of -9.2 kcal/mol, and formed hydrophobic contacts with Trp83, Phe330 and His439 residues localized in the catalytic triad of the enzyme (Hussein et al, 2019). In another in silico study, δ-cadinene exhibited a binding affinity of -6.77 kcal/mol to AChE, the target protein of Alzheimer's disease, and formed pi-alkyl bonds with polar aliphatic residues Trp286 and His447, and hydrophobic contacts with hydrophobic residues Tyr124 and Phe295 (da Silva Barbosa et al, 2020).…”
Section: Molecular Docking Results Of Essential Oil Major Compoundsmentioning
confidence: 99%
“…However, viridiflorol exhibits a more favorable drug-like profile since it does not exceed the MLOGP > 4.15 limit that is violated by the other four ligands. As a result, the 'hit' ligands δ-cadinene, viridiflorol, γ-muurolene and αcaryophyllene, in general, show good pharmacokinetic activity and low toxicity (da Silva Barbosa et al, 2020;Hussein et al, 2019;Schepetkin et al, 2021). Cytochrome P450 (CYP) inhibition, on the other hand, is a common handicap observed in all ligands, and may have adverse effects on the drug metabolism of the host organism.…”
Section: Admet and Drug-likeness Features Of Hit Compoundsmentioning
confidence: 99%
“…Also, it can be utilized as a biological insecticide on date palm aphids (Al-Keridis, 2022). Some other studies have ascertained the potency of myrrh as an antibacterial, antifungal, antiparasitic, and bio-insecticide natural agent (Allam et al, 2001;Sheir et al, 2001;Perveen et al, 2018;Becheker et al, 2022;).The efficiency of myrrh oil may be attributed to its mode of action as Acetyl Choline esterase (AChE) inhibitor as described by (Hussein et al, 2019) who found that the botanical extracts resulted from leaves, bark, and resin of C. myrrha caused inhibition of AChE activity by 17, 26, and 29% for leaves, bark, and resin respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a comprehensive evaluation of ADMET indicated that cedrelanol has the capability to traverse the gastrointestinal tract and the blood-brain barrier. In the context of antibacterial activity and its potential to inhibit cholera toxin-induced intestinal hypersecretion, it is worth noting that the sesquiterpene T-cadinol, isolated from the aromatic resin of Commiphora guidottii (Burseraceae), commonly referred to as scented myrrh, has been documented [46]. Cholera infection is sometimes characterized by the presence of severe electrolyte imbalances and acute kidney injury or inflammation.…”
Section: Discussionmentioning
confidence: 99%